2003
DOI: 10.1046/j.1365-246x.2003.01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Geothermal characteristics of the Ries impact structure

Abstract: SUMMARY A new investigation of the thermal conductivity of the drill cores from the research drill hole Nördlingen 1973 in the Ries impact structure was conducted. The 1206 m deep drill hole penetrated 331 m of post‐impact lake formations, then 275 m of suevitic impact formations with varying amounts of large crystalline basement blocks and then 600 m of fractured, displaced basement blocks containing appreciable amounts of dyke breccias. The main purpose of the measurements was to see the signature of the sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…A possible interpretation of this result is that the rock retains extensive microcrack damage and, further, that the degree of this damage decreases with depth. These results appear to be in qualitative agreement with the recent thermal conductivity measurements of Popov et al (2003) on archived core obtained from the Nördlingen 1973 research borehole drilled in the Ries impact structure. Thermal conductivity was found to generally increase with depth, as did the P-wave sonic log velocities.…”
Section: Open Hole Sectionsupporting
confidence: 90%
“…A possible interpretation of this result is that the rock retains extensive microcrack damage and, further, that the degree of this damage decreases with depth. These results appear to be in qualitative agreement with the recent thermal conductivity measurements of Popov et al (2003) on archived core obtained from the Nördlingen 1973 research borehole drilled in the Ries impact structure. Thermal conductivity was found to generally increase with depth, as did the P-wave sonic log velocities.…”
Section: Open Hole Sectionsupporting
confidence: 90%
“…Investigations performed in recent years at the Vorotilovo scientific deep well drilled in the Puchezh‐Katunk impact structure, Russia [ Popov et al , 1998], and at the Nördlingen‐1973 scientific well drilled in the Ries impact structure, Germany [ Popov et al , 2003a], demonstrated (1) low thermal anisotropy of rocks (brecciated, cataclased, thermally overprinted and shock transformed target rocks) and (2) low values of thermal conductivity, density and velocity in the rocks affected by the shock and postshock thermal conditions [ Schmitt et al , 2007] in comparison with similar rocks outside these impact structures.…”
Section: Introductionmentioning
confidence: 99%
“…These peculiarities may be typical of impact structures in general and can be caused by mechanical damage and the shock‐induced thermal metamorphism of rocks [e.g., Popov et al , 1998, 2003a; Vermeesch and Morgan , 2004]. Nevertheless, this question can only be answered by taking into account the lithology of the impact structures.…”
Section: Introductionmentioning
confidence: 99%
“…), the Ries impact structure (the Noerdlingen‐73 borehole, Germany; Popov et al. ), the Chicxulub structure (the Yaxcopoil‐1 borehole, Mexico; Popov et al. , ; Wilhelm et al.…”
Section: Introductionmentioning
confidence: 99%
“…); the rock anisotropy was taken into account at these measurements (Popov et al. , , , ; Mayr et al. , ).…”
Section: Introductionmentioning
confidence: 99%